1994
DOI: 10.4049/jimmunol.152.3.1127
|View full text |Cite
|
Sign up to set email alerts
|

Fas antigen is the major target molecule for CD4+ T cell-mediated cytotoxicity.

Abstract: Activation of the Fas cell surface molecule, either by specific antibody or by its as yet unidentified ligand, has been shown to induce apoptosis. Because apoptosis is also evoked in target cells by cytolytic T cells, we investigated whether the Fas pathway is involved in CD4+ T cell-mediated cytotoxicity. Analysis of Fas expression in APC, such as the B lymphoma A20.2J and MHC class II-transfected fibroblasts RT2.3, revealed a correlation between the degree of expression and sensitivity to cytotoxic attack, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Furthermore, it has been shown that the CD4 + T cells in carp ( Carassius auratus langsdorfii ) have strong direct antibacterial activity (Nayak and Nakanishi 2013 ). In mammals, CD4 + Tc cells have also been investigated, and they were found to function using the same cytolytic pathways as those in CD8 + Tc cells (Appay et al 2002 ; Hashimoto et al 2019 ; Stalder et al 1994 ; Williams and Engelhard 1996 ). However, the precise roles of CD4 + Tc cells remain unclear.…”
Section: Diversity Of Cd4 Molecules and Cd4 + T Ly...mentioning
confidence: 99%
“…Furthermore, it has been shown that the CD4 + T cells in carp ( Carassius auratus langsdorfii ) have strong direct antibacterial activity (Nayak and Nakanishi 2013 ). In mammals, CD4 + Tc cells have also been investigated, and they were found to function using the same cytolytic pathways as those in CD8 + Tc cells (Appay et al 2002 ; Hashimoto et al 2019 ; Stalder et al 1994 ; Williams and Engelhard 1996 ). However, the precise roles of CD4 + Tc cells remain unclear.…”
Section: Diversity Of Cd4 Molecules and Cd4 + T Ly...mentioning
confidence: 99%
“…As células T CD4 + atuam classicamente como reguladoras e efetoras da resposta imune a patógenos por meio da produção de citocinas, entretanto há mais de duas décadas têm sido descrito a seu importante papel na resposta citotóxica, tanto em camundongos quanto em humanos contra aloantígenos, células infectadas por microrganismos e células cancerígenas Kresnky et al, 1982;Lewinsohn et al, 1998b;Lukacher et al, 1985;McCarthy et al, 1986;Paludan et al, 2002). Os primeiros estudos mostraram que as células T CD4 + citotóxicas agiam preferencialmente pela interação CD95/CD95L (Hanabuchi et al, 1994;Ju et al 1994;Stalder et al, 1994;Williamns e Engelhard, 1996). Entretanto posteriormente foi demonstrado células CD4 + citotóxicas também utilizam a perforina e a exocitose de granzimas (Hahn et al, 1999;Williams e Engelhard, 1997).…”
Section: Discussionunclassified